Local Product Patronage Among Senior High School Students (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Patronage of local products is important for molding community resilience, economic sustainability, and cultural preservation. With the expanding influence of globalization, people are becoming more accustomed to preferring non-local products. This study aims to investigate the respondent’s patronage to local products to come up with an advocacy material to promote these goods. The study utilized quantitative descriptive-survey design, gathering data from 180 senior high school students enrolled at Union Christian College using adapted questionnaires. Weighted mean and standard deviation were the primary data gathering tools used in analyzing the data. The findings revealed that while they believe patronage to local food can promote local culture, the respondents moderately patronize local cuisine as they prefer fast food, and that local cuisines have less variety of flavors. Also, they moderately patronize local clothing since these products are more expensive than those that are commercially produced. Moreover, the moderately patronize local household products because they prefer modernized plastic products that are cheaper. They perceive that price, product quality, brand recognition, accessibility, taste preference, online shopping trends, peer, and family influence their patronage to local products. It can be implied that there is a need to improve the patronage of the respondents to local product to build stronger cultural identity and help folks who are still offering these products. The researchers recommend that an advocacy material geared towards the promotion of local products be cascaded to the community to increase their patronage towards them.
Keywords: local products; patronage; cultural heritage